The Influence of Financial Performance and Corporate Governance Mechanism on Capital Structure - Lusiana, Emi; Sudarma, Ketut (Management Analysis Journal, 2018)
The research aims to determine whether asset structure, firm size, profitability, growth sales, board size, and institutional ownership on the capital structure. The population of this research are all mining and mining service companies listed in Indonesia Stock Exchange period 2012-2016. The sample are 27 companies, so the data observation as much as 135 data. The data analysis technique used was linier regression analysis with Random Effect Model approach. The result of data analysis showed that profitability and growth sales have significant affect on capital structure. Profitability have significant negative affect and growth sales have significant positive affect. The conclusion of this research showed that the capital structure on mining and mining service was influenced by profitability and growth sales, while asset structure, firm size, board size and institutional ownership did not have significant affect. The writer suggeststhat the company should improve profitability by increasing company’s sales and stable sales growth in order to reduce the company’s dependence on debt.